ANALISIS IMPLEMENTASI LIFE SKILLS OLEH GURU DAN SISWA SDIT PERMATA BUNDA BATANG - Ilma Ludvitasari; Arfilia Wijayanti; M.Yusuf Setia Wardana (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2022)
The purpose of this study was to find out about how the implementation of Life Skills by teachers and students at SDIT Permata Bunda Batang. The type of research used is qualitative research which obtains data from interview, observation, questionnaire and documentation. The data that has been collected is processed by triangulation technique and explained using descriptive methods written according to the data sources obtained in the field. The results of this study indicate that the implementation of Life Skills carried out at the SDIT Permata Bunda Batanghas been carried out according to very good habits, with an average teachers score of 95,13%, and students who get an average score of 80,48%. So it can be concluded that the implementation of Life Skills by teachers and students at SDIT Permata Bunda Batang walked with a high percentage gain in the very good category.